Complete Resolution of TAFRO Syndrome (Thrombocytopenia, Anasarca, Fever, Reticulin Fibrosis and Organomegaly) after Immunosuppressive Therapies using Corticosteroids and Cyclosporin A : A Case Report - Inoue, Morihiro; Ankou, Mayuka; Hua, Jiang; Iwaki, Yasunobu; Hagihara, Masao; Ota, Yasunori (Journal of Clinical and Experimental Hematopathology, 2013)
A 49-year-old woman with severe thrombocytopenia was admitted after an episode of syncope. She also had anemia, fever, pleural effusion and ascites, and multiple lymphadenopathies subsequently appeared. Her bone marrow showed increased megakaryocytes with mild fibrosis, whereas her lymph nodes lacked histologically specific findings. Her presentation was not consistent with multicentric Castleman's disease, angioimmunoblastic T-cell lymphoma, systemic lupus erhythematosus or any other well-recognized entities. Her clinical features were, however, thought to be compatible with TAFRO (thrombocytopenia, anasarca, fever, reticulin fibrosis, and organomegaly) syndrome. Corticosteroid therapy induced a partial remission of fever and systemic fluid retention, but thrombocytopenia persisted. After additional immunosuppressive therapy with cyclosporin A, her symptoms showed full resolution. [J Clin Exp Hematop 53(1) : 95-99, 2013]